Evaluation of the role of clean energy technologies, human capital, urbanization, and income on the environmental quality in the United States - Pata, Ugur Korkut; Caglar, Abdullah Emre; Kartal, Mustafa Tevfik; Depren, Serpil Kilic (ELSEVIER SCI LTD, 2023)
In today's world, environmental concerns are at the forefront of countries' considerations, along with economic priorities. In this context, countries face the challenge of developing and directing their investments in clean energy technologies to achieve the Sustainable Development Goals, particularly affordable and clean energy. Does the development and diffusion of clean energy technologies contribute to improving environmental qual-ity? This study addresses this question by examining the effects of clean energy technologies on sustainable environmental quality as expressed by the load capacity factor (LCF). In this context, the study explores the United States (US), as the largest economy and one of the leading countries investing in clean energy, considering the role of human capital, urbanization, and economic growth. To this end, this paper applies the novel augmented autoregressive distributed lag (ARDL) model to annual data from 1974 to 2018. The long-term empirical results show that (i) Clean energy technologies have no effect on the LCF; (iii) human capital sup-ports environmental quality; (iv) urbanization has an adverse effect on environmental quality; (v) increasing economic growth worsens environmental quality. Overall, the empirical results suggest that while clean energy technologies should support sustainable environmental quality, this is unfortunately not the case in the US. Therefore, the US policymakers need to take improvement actions to ensure that clean energy technologies contribute to sustainable environmental quality and that the community reaps the environmental benefits of human capital.
Keywords: Clean energy technologies; Environmental quality; Human capital; Load capacity factor; Fourier transform; CO2 EMISSIONS; EMPIRICAL-EVIDENCE; SUSTAINABILITY; CONSUMPTION; TRADE; INNOVATION; WORLD; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology